Evaluating the Effectiveness of Psychological Interventions in Patients with Psoriasis: A Review. Issue 1 (March 2014) - Tran, Anh N.; Koo, John Y.
Psoriasis is a common condition, often associated with substantial psychological morbidity. Stress is frequently implicated in the onset or exacerbation of psoriasis, giving rise to the possible use of psychotherapeutic modalities in treatment. This article reviewed the literature describing cases and trials of psychological interventions (i.e., psychotherapy, biofeedback, hypnosis, meditation, and emotional disclosure) in the treatment of patients with psoriasis. All six case reports/series demonstrated positive outcomes. Among the trials, seven out of 11 found significant physical improvement and four out of seven found significant psychological benefit. Psychological interventions appear to have the potential to serve as helpful adjuncts to conventional dermatological treatments, although further research is needed with emphasis on randomized controlled trials with more standardized, validated outcome measures.